2006
DOI: 10.21608/kvmj.2006.112476
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and Biochemical Changes of the Washed Buffalo Spermatozoa Added With Caffeine

Abstract: Twelve sexually mature buffalo bulls, were used in the present study. The experimental work was carried out to study the effects of removal of seminal plasma by centrifugation and addition of different concentrations of caffeine (0,2,4 and 8mM/100ml) to the extended cooled buffalo semen with lactose-yolk citrate (LYC) extender on biophysical (percentage of sperm motility, dead spermatozoa, sperm abnormalities and acrosomal damage) and biochemical (aspartateaminotransferase: AST, alanine-aminotransferase: ALT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…As expected, the values of ALT, AST, ALP and hyaluronidase enzymes were significantly reduced upon addition of caffeine due to the stabilizing impact of caffeine on cellular membrane (Abd Shukla andMisra, 2014). Matching with our results, addition of caffeine to the diluted cooled buffalo bull spermatozoa decreased the amounts of AST, ALT and ALP enzymes released into the extracellular medium (Zeidan et al, 2006). Activities of glutathione-S-transferases (GSTs) were decreased (P<0.01) with all caffeine samples compared with the control sample (El-Kishk, 2003 andChavda et al, 2022).…”
Section: Impact Of Seminal Plasma Removal And/or Caffeine Supplementa...supporting
confidence: 89%
See 1 more Smart Citation
“…As expected, the values of ALT, AST, ALP and hyaluronidase enzymes were significantly reduced upon addition of caffeine due to the stabilizing impact of caffeine on cellular membrane (Abd Shukla andMisra, 2014). Matching with our results, addition of caffeine to the diluted cooled buffalo bull spermatozoa decreased the amounts of AST, ALT and ALP enzymes released into the extracellular medium (Zeidan et al, 2006). Activities of glutathione-S-transferases (GSTs) were decreased (P<0.01) with all caffeine samples compared with the control sample (El-Kishk, 2003 andChavda et al, 2022).…”
Section: Impact Of Seminal Plasma Removal And/or Caffeine Supplementa...supporting
confidence: 89%
“…Activities of glutathione-S-transferases (GSTs) were decreased (P<0.01) with all caffeine samples compared with the control sample (El-Kishk, 2003 andChavda et al, 2022). Results recorded that RSP reduced ALT, AST, ALP and hyaluronidase enzymes which may be related to the removal of the inhibitory factors presented in seminal plasma that causes the breakdown of sperm membrane and ease of enzymatic leakage from intracellular to extracellular fluids of spermatozoa (Sengupta et al, 1976, Zeidan et al, 2004, Bahgat, 2008and Daramola, 2017.…”
Section: Impact Of Seminal Plasma Removal And/or Caffeine Supplementa...mentioning
confidence: 98%
“…In accordance these results, Akandi et al (2015) found that propolis supplementation with a semen extender improves sperm viability and DNA integrity. In addition, extenders containing propolis were reported to lower the release of enzymes such as ALT, AST, ALP, and LDH significantly into the sperm medium (Mohamed and Zanouny, 2017;Mohamed, 2017) which may reflect the high sperm membrane integrity during incubation and storage (Zeidan et al, 2004). Improving sperm characteristics in pre-freezing and post-thaw semen was explained by several authors.…”
Section: Figurementioning
confidence: 98%